Sodium Chloride Added to Diluted Concord Grape Juice Prior to Fermentation Results in a Highly Attractive Bait for Drosophila suzukii (Diptera: Drosophilidae) - Piñero, Jaime C.; Godoy-Hernandez, Heriberto; Giri, Ajay; Wen, Xiaojian (Frontiers in Ecology and Evolution, 2022)
At the interface of behavioral chemical ecology and pest management lays the evaluation of kairomones that can be used for either, monitoring or attract-and-kill of insect pests. Diluted Concord grape juice (DGJ) was previously reported to be highly attractive to male and female D. suzukii. Here, we conducted cage and field studies aimed at (1) comparing the attractiveness of fresh DGJ against that of commercial lures over a 3-year period in multiple locations, (2) quantifying the effects of DGJ aging for 1 and 2 weeks on D. suzukii attraction, and (3) ascertaining the effects of adding sodium chloride to DGJ prior to fermentation on the outcome. For all field studies, captures of non-target insects were recorded. Combined findings from the cage and field studies comparing DGJ and commercial lures indicate that fresh DGJ is as attractive or more attractive than the commercial lures that were evaluated. The results of the aging studies revealed that 7- and 14- day old DGJ baits are at least twice as attractive to female D. suzukii when compared to fresh DGJ. The response of other Drosophilids to the aged olfactory treatments mirrored that of D. suzukii. Remarkably, the addition of 2% sodium chloride to DGJ prior to aging resulted in a 4-fold increase in attractiveness to male and female D. suzukii while reducing the number of non-target insects captured in traps. In conclusion, DGJ is an effective bait that can be deployed in traps and, when 2% sodium chloride is added the resulting material outcompetes the performance of commercial lures and greatly reduces captures of non-target insects, thereby increasing bait selectivity. Overall, our findings increase our understanding of D. suzukii olfactory-driven behavior in response to fruit-based odor and demonstrate the potential use of a low-cost attractants for farmers who are not able to monitor for D. suzukii when commercially produced lures are expensive or less accessible.